A Comprehensive Review: Genetic Mapping of Genes Associated with Green Leaf Color Variations in Main Vegetable Crops - Menghao Wang; Xinyin Wang; Yue Wang; Xiyue Yang; Xiabing Li; Junrong Chen; Shengjun Feng (Plants)
The diversity in the coloration of vegetable leaves carries substantial commercial and nutritional importance. Investigating mutants of vegetable leaf color is of paramount importance for uncovering the mechanisms behind leaf color variation and for developing new high-yielding vegetable varieties with enhanced photosynthetic efficiency. This paper encapsulates the principal advancements in research concerning vegetable leaf color mutants, elucidates the origins and gene mapping techniques for these mutants, and delineates the molecular regulatory mechanisms involved in leaf color transformation. The findings presented serve as a valuable reference for the cultivation of superior plant material and for fostering the sustainable growth of vegetable cultivation practices.